Pertumbuhan tiram mutiara (Pinctada maxima) menggunakan metode karambah apung dan longline: Pearl oyster (Pinctada maxima) growth using floating cage and longline methods - Gladys Indri Hendrawati; Ummul Firmani (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2024)
Pearl oyster cultivation is a growing industry in various countries. The growth and quality of pearls produced by oysters is greatly influenced by the cultivation method used. This research aims to compare the growth of pearl oysters (Pinctada maxima) cultivated using the floating cage and longline methods. Different cultivation methods can influence the growth of pearl oysters and the surrounding environmental conditions. Statistical analysis was conducted on sample size, mean values, standard deviation, and standard error of the mean for both cultivation methods. The results indicate no significant difference in the growth of pearl oysters between the floating cage and longline methods. However, biofouling and other disrupting organisms can affect the growth of pearl oysters in the floating cage method. The study also highlights the importance of environmental factors such as water quality, temperature, and food availability in influencing the growth of pearl oysters. Thus, this research provides valuable insights for the pearl oyster cultivation industry in selecting the optimal cultivation method to enhance productivity and the quality of the pearls produced.